Internalisasi Nilai-Nilai Tauhid dalam Kurikulum Pendidikan Islam - Fadli, Dastur (Jurnal Ilmiah Guru Madrasah, 2025)
The values of monotheism are the main foundation in all aspects of Muslim life, including the education system. The Islamic education curriculum is not only oriented towards cognitive aspects, but also towards character and moral formation based on monotheism. This study aims to examine the concept of internalizing the values of monotheism in the Islamic education curriculum, both at the philosophical level, in terms of objectives, and in practical implementation in educational institutions. The research method used is a qualitative-descriptive approach with literature analysis (library research). The results of the study show that the internalization of tauhid values can be realized through three main approaches: the integration of tauhid values in all subjects, habituation in learning activities and school life, and the exemplary behavior of educators as representatives of tauhid values.